Saosys toolbox as Matlab implementation in the elastic‐plastic analysis and optimal design of steel frame structures - Jankovski, Valentinas; Atkočiūnas, Juozas (Journal of Civil Engineering and Management, 2010)
The improved mathematical model of steel frame structures’ design is created. The loading is simple, and plastic strains are evaluated. Energy principles of deformable body mechanics and mathematical programming theory are employed. Equilibrium finite elements with interpolation functions of internal forces are used for discretization. The elements are designed using HE, IPE, RHS steel profile assortments and considering dispersion of geometrical characteristics of profile assortment sets. Optimal design of steel structures is realized by using the experimental tool system JWM SAOSYS Toolbox v0.42, which was created by the authors in MATLAB environment. SAOSYS architecture operates with object‐oriented finite elements pseudo‐polymorphously. The possibilities of this system are demonstrated by considering a numerical example of optimal design of industrial building frame with strength and stiffness constraints. The assumption of small displacements is adopted for computations.Published Published Online: 14 Oct 2010